Global analysis of μ → e interactions in the SMEFT - Filippo Delzanno; Kaori Fuyuto; Sergi Gonzàlez-Solís; Emanuele Mereghetti (Journal of High Energy Physics)
Abstract We study current experimental bounds on charged lepton flavor violating (CLFV) μ – e interactions in the model-independent framework of the Standard Model Effective Field Theory (SMEFT). Assuming a generic flavor structure in the quark sector, we consider the contributions of CLFV operators to low-energy observables, including μ → eγ and μ → e conversion for quark-flavor conserving operators and CLFV meson decays for quark-flavor violating operators. At high energy, we consider limits on CLFV decays of the Higgs and Z bosons and of the top quark, and obtain bounds on operators with light quarks by recasting searches for production of eμ pairs in pp collisions at the Large Hadron Collider (LHC). We connect observables at low- and high-energy by taking into account renormalization group running and matching between CLFV operators. We also discuss the sensitivity of the future Electron-Ion Collider, where the prospective bounds are derived by imposing simple cuts on final state particles. We find that, in a single operator scenario, bounds on purely leptonic operators are dominated by μ → eγ and μ → e conversion. Semileptonic operators with down-type quarks are also dominantly constrained by low-energy observables, while LHC searches lead the bounds on up-type quark-flavor violating operators. Taking simplified multiple-coupling scenarios, we show that it is easy to evade the strongest low-energy bounds from spin-independent μ → e conversion, and that collider searches are competitive and complementary to constraints from spin-dependent μ → e conversion and other low-energy probes.